Dietary strategies with anti-aging potential: Dietary patterns and supplements. (August 2022) - Duan, Hui; Pan, Jiani; Guo, Min; Li, Jinwei; Yu, Leilei; Fan, Liuping
Graphical abstract: Highlights: Okinawan, Medit, DASH diets, CR and IF are reliable dietary patterns for anti-aging. Ketogenic diet is a controversial dietary pattern for anti-aging. Combined use of dietary patterns and supplements can achieve additive effects. Nutrigenomics plays a vital role in personalized dietary strategy. Identifying accurate aging biomarkers is crucial to precise dietary intervention. Abstract: Dietary intervention is a safe, broad-spectrum, and low-cost preventive strategy for slow aging. The Okinawan, Mediterranean, and Dietary approaches to stop hypertension (DASH) diets, as well as caloric restriction (CR) and intermittent fasting (IF), are classic and reliable dietary patterns that slow aging by regulating nutrient-sensing pathways, gut microbiota, metabolism, and immunity. Moreover, the proportion of the three macronutrients (carbohydrate, protein and fat) is also vital for slowing aging, but the debates about the appropriate proportion, especially the ratio of carbohydrates and proteins, remain unknown. Strict and lifelong adherence to these regimens is difficult, thereby promoting the emergence of various dietary supplements, including natural CR mimics, probiotics, natural senolytics, vitamins and essential minerals. Combinations of different dietary patterns and supplements with distinct pathways may have additive effects. Individuals' aging speed and dietary response are highly variable, thus highlighting the need for precise anti-aging dietary intervention. Nutrigenomics plays an important role in personalized dietary strategies. Therefore, this review critically compares the anti-aging effects of various dietary patterns and supplements, analyzes their mechanisms and combined use, and proposes future research directions to achieve personalized dietary strategies for slowing aging.